The Gapless Design for High Sensitivity of Current Mode Dual Magnetodiode - Chalin Sutthinet; Sawatdipong Poonsawat; Toempong Phetchakul; Amporn Poyai (My University, 2019)
This paper presents the design for high sensitivity of magnetic detector device in current mode that uses Lorentz's force deflects current depend on the magnetic density via the dual magnetodiode structure. The current mode devices have two symmetry regions for carrier current receiving that injected from another opposite region. This design has a gap between two carrier current receiving regions that causes some loss and reduce sensitivity. The proposed design has one carrier current receiving region or gapless design that has no loss from gap. The sensitivities of gap 5, 2.5 and 0 μm at 1 mA are 0.0010, 0.0028 and 0.0065 T−1 for split cathode structure and 0.00084, 0.0020 and 0.0051 T−1 for split anode structure, respectively. This design can be applied to all current mode magnetic device for high sensitivity.
Keywords: Gapless playback; Lorentz force; Dual mode; Magnetic Field Sensors Techniques